Cellular and Molecular Pathways Leading to External Root Resorption. (February 2017) - Iglesias-Linares, A.; Hartsfield, J.K.
External apical root resorption during orthodontic treatment implicates specific molecular pathways that orchestrate nonphysiologic cellular activation. To date, a substantial number of in vitro and in vivo molecular, genomic, and proteomic studies have supplied data that provide new insights into root resorption. Recent mechanisms and developments reviewed here include the role of the cellular component—specifically, the balance of CD68 +, iNOS + M1- and CD68 +, CD163 + M2-like macrophages associated with root resorption and root surface repair processes linked to the expression of the M1-associated proinflammatory cytokine tumor necrosis factor, inducible nitric oxide synthase, the M1 activator interferon γ, the M2 activator interleukin 4, and M2-associated anti-inflammatory interleukin 10 and arginase I. Insights into the role of mesenchymal dental pulp cells in attenuating dentin resorption in homeostasis are also reviewed. Data on recently deciphered molecular pathways are reviewed at the level of (1) clastic cell adhesion in the external apical root resorption process and the specific role of α/β integrins, osteopontin, and related extracellular matrix proteins; (2) clastic cell fusion and activation by the RANKL/RANK/OPG and ATP-P2RX7-IL1 pathways; and (3) regulatory mechanisms of root resorption repair by cementum at the proteomic and transcriptomic levels.